1999
DOI: 10.1074/jbc.274.19.13229
|View full text |Cite
|
Sign up to set email alerts
|

Unusual Sites of Arginine Methylation in Poly(A)-binding Protein II and in Vitro Methylation by Protein Arginine Methyltransferases PRMT1 and PRMT3

Abstract: Arginine methylation is a post-translational modification found mostly in RNA-binding proteins. Poly(A)-binding protein II from calf thymus was shown by mass spectrometry and sequencing to contain N G ,N G -dimethylarginine at 13 positions in its amino acid sequence. Two additional arginine residues were partially methylated. Almost all of the modified residues were found in Arg-Xaa-Arg clusters in the C terminus of the protein. These motifs are distinct from Arg-Gly-Gly motifs that have been previously descri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
164
0
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 144 publications
(166 citation statements)
references
References 49 publications
1
164
0
1
Order By: Relevance
“…The predicted molecular weight of PABP2 is ;33 kDa (Nemeth et al+, 1995) and therefore, if the protein is present in the cell as free monomers, it is expected to passively diffuse through the pores and therefore equilibrate between the nucleus and the cytoplasm+ However, our finding that PABP2 targets to the nucleus a fusion protein (luciferase-PABP2, predicted molecular weight ;90 kDa) that is too large to cross the pores by simple diffusion provides evidence for involvement of a carrier-mediated mechanism+ This is further supported by the result that PABP2 binds directly and specifically to the nuclear import receptor transportin+ Until a few years ago, nuclear import studies were centered on proteins carrying either a mono-or a bipartite NLS being recognized by a heterodimeric carrier named importin a/b+ However, recent work led to the discovery of a second pathway for protein import mediated by an importin-b-related protein, termed transportin in mammals (Pollard et al+, 1996) and Kap104p in yeast (Aitchison et al+, 1996)+ In mammals transportin mediates import of a subset of hnRNP proteins, the best characterized of which is hnRNP A1 (Pollard et al+, 1996;Siomi et al+, 1997)+ The signal within hnRNP A1 that mediates its nuclear import is a stretch of 38 C-terminal amino acids termed the M9 domain (Siomi & Dreyfuss, 1995)+ Because hnRNP proteins are very abundant (10 6 -10 7 copies per cell), it has been speculated that transportin has evolved as a specialized carrier for these high abundance substrates, contrasting with the importin-a/b carrier that recognizes a broad range of cargoes but with most members present at relatively low abundance (Nigg, 1997)+ The data presented here demonstrate that PABP2 binds directly to transportin, thus providing evidence that PABP2 is a novel substrate for this carrier+ Importantly, PABP2 dissociates from transportin in the presence of RanGTP, suggesting that, in vivo, the high concentration of RanGTP in the nucleus triggers release of the cargo (PABP2) into the nucleoplasm, as previously demonstrated for the importin-a/b-mediated import pathway Izaurralde et al+, 1997b;Siomi et al+, 1997)+ The data also suggest that the NLS of PABP2 is contained in its C-terminal domain+ However, the C-terminal sequence of PABP2 (Fig+ 3, bottom diagram) shows no apparent homology with the M9 signal, raising the possibility that it represents a novel type of NLS+ An interesting feature of the C-terminus of PABP2 is that it is very rich in arginine residues, almost all of which are dimethylated (Smith et al+, 1999)+ N G ,N Gdimethylarginine is also a common modified amino acid in hnRNP proteins (Beyer et al+, 1977;Boffa et al+, 1977), and more recently, arginine methylation was shown to be important for the nuclear export of shuttling hnRNP proteins in yeast (Shen et al+, 1998)+ Therefore, an important question to be addressed in future studies is whether dimethylated arginines in the C-terminal domain of PABP2 play a role in transport of the protein in and out of the nucleus+…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The predicted molecular weight of PABP2 is ;33 kDa (Nemeth et al+, 1995) and therefore, if the protein is present in the cell as free monomers, it is expected to passively diffuse through the pores and therefore equilibrate between the nucleus and the cytoplasm+ However, our finding that PABP2 targets to the nucleus a fusion protein (luciferase-PABP2, predicted molecular weight ;90 kDa) that is too large to cross the pores by simple diffusion provides evidence for involvement of a carrier-mediated mechanism+ This is further supported by the result that PABP2 binds directly and specifically to the nuclear import receptor transportin+ Until a few years ago, nuclear import studies were centered on proteins carrying either a mono-or a bipartite NLS being recognized by a heterodimeric carrier named importin a/b+ However, recent work led to the discovery of a second pathway for protein import mediated by an importin-b-related protein, termed transportin in mammals (Pollard et al+, 1996) and Kap104p in yeast (Aitchison et al+, 1996)+ In mammals transportin mediates import of a subset of hnRNP proteins, the best characterized of which is hnRNP A1 (Pollard et al+, 1996;Siomi et al+, 1997)+ The signal within hnRNP A1 that mediates its nuclear import is a stretch of 38 C-terminal amino acids termed the M9 domain (Siomi & Dreyfuss, 1995)+ Because hnRNP proteins are very abundant (10 6 -10 7 copies per cell), it has been speculated that transportin has evolved as a specialized carrier for these high abundance substrates, contrasting with the importin-a/b carrier that recognizes a broad range of cargoes but with most members present at relatively low abundance (Nigg, 1997)+ The data presented here demonstrate that PABP2 binds directly to transportin, thus providing evidence that PABP2 is a novel substrate for this carrier+ Importantly, PABP2 dissociates from transportin in the presence of RanGTP, suggesting that, in vivo, the high concentration of RanGTP in the nucleus triggers release of the cargo (PABP2) into the nucleoplasm, as previously demonstrated for the importin-a/b-mediated import pathway Izaurralde et al+, 1997b;Siomi et al+, 1997)+ The data also suggest that the NLS of PABP2 is contained in its C-terminal domain+ However, the C-terminal sequence of PABP2 (Fig+ 3, bottom diagram) shows no apparent homology with the M9 signal, raising the possibility that it represents a novel type of NLS+ An interesting feature of the C-terminus of PABP2 is that it is very rich in arginine residues, almost all of which are dimethylated (Smith et al+, 1999)+ N G ,N Gdimethylarginine is also a common modified amino acid in hnRNP proteins (Beyer et al+, 1977;Boffa et al+, 1977), and more recently, arginine methylation was shown to be important for the nuclear export of shuttling hnRNP proteins in yeast (Shen et al+, 1998)+ Therefore, an important question to be addressed in future studies is whether dimethylated arginines in the C-terminal domain of PABP2 play a role in transport of the protein in and out of the nucleus+…”
Section: Discussionmentioning
confidence: 99%
“…PABP2 shuttles between nucleus and cytoplasm+ HeLa cells were immunostained with affinity-purified anti-PABP2 antibodies (A) and hybridized with a poly(U) riboprobe (B)+ PABP2 is detected exclusively in the nucleoplasm whereas poly(A) RNA is detected in both cytoplasm and nucleoplasm+ Within the nucleoplasm, PABP2 and poly(A) RNA colocalize in speckles (arrows)+ C-E: HeLa cells were fused with Drosophila SL2 cells to form heterokaryons+ HeLa cells were treated with emetine for 3 h before fusion+ After fusion the cells were kept in culture for 3 h in the presence of emetine+ Heterokaryons were fixed and double-labeled with affinity-purified anti-PABP2 antibodies (C) and monoclonal 4F4 directed against hnRNP C (D)+ E shows the corresponding phase-contrast image+ F: The affinity-purified anti-PABP2 antibodies do not react with SL2 nuclei+ G shows the corresponding phase-contrast image+ Bar ϭ 10 mm+ Nuclear import of PABP2 is carrier mediated PABP2 is a small protein (;33 kDa) that may cross the diffusion channel of nuclear pore complexes+ A possible explanation for the observed nucleocytoplasmic shuttling could therefore be that PABP2 diffuses bidirectionally through the pores but is predominantly retained in the nucleus as it binds to the growing poly(A) tails+ To address this question, we analyzed the nucleocytoplasmic distribution of PABP2 fused to nonnuclear proteins+ As reporter proteins we used GFP (;27 kDa) and a form of firefly luciferase (;60 kDa) containing a Leu r Val mutation that disrupts its peroxisomal targeting signal (Gould et al+, 1989)+ As expected for relative small proteins with no specific retention in any subcellular compartment, both GFP and luciferase appear distributed throughout the cytoplasm and the nucleus (Fig+ 2A,C)+ In contrast, the chimeras GFP-PABP2 and luciferase-PABP2 are exclusively detected in the nucleus, excluding nucleoli (Fig+ 2B,D)+ Moreover, both chimeras have a speckled distribution pattern in the nucleoplasm similar to endogenous PABP2 (cf+ Fig+ 1A)+ Because the fusion protein luciferase-PABP2 is too large (;90 kDa) to enter the diffusion channel of nuclear pores, we conclude that import of PABP2 into the nucleus involves a carrier-mediated mechanism+ A key feature of carrier-mediated nuclear transport is the recognition of specific signals present in the substrate proteins+ We therefore asked which domains of PABP2 are important for its nuclear import+ To investigate a potential role of the RNA-binding domain in nuclear import, we analyzed the nucleocytoplasmic distribution of a mutant form of PABP2 (dmPABP2), which contains a double-point mutation in the RNA-binding domain (phenylalanine to alanine at position 215 and tyrosine to alanine at position 175)+ In vitro, this mutant binds to poly(A) approximately 20-fold less than wildtype PABP2 (Nemeth, 1998)+ Both GFP-dmPABP2 and luciferase-dmPABP2 chimeras are exclusively detected in the nucleus (Fig+ 3A and data not shown)+ However, in contrast with wild-type chimeras, the dmPABP2 fusion proteins are uniformly distributed in the nucleoplasm, with no concentration in speckles+ Since poly(A)-enriched speckles persist in these cells, the lack of accumulation of dmPABP2 in these structures most likely reflects failure of the mutant protein to interact with poly(A) RNA (to be described in detail elsewhere)+ Thus, nuclear targeting of PABP2 appears independent of RNA binding+ PABP2 contains two additional structural motifs, an acidic N-terminal domain containing basic patches and an arginine-rich C-terminal domain+ We therefore analyzed the localization pattern of both N-and C-terminal deletion mutants+ ⌬NPABP2 contains a deletion of amino acids 1-160, ⌬CPABP2 contains a deletion of amino acids 257-306 (Smith et al+, 1999), and CPABP2 contains only the C-terminal domain (amino acids 256-306)+ The fusion GFP-⌬NPABP2 is exclusivel...…”
Section: Pabp2 Shuttles Between the Nucleus And The Cytoplasmmentioning
confidence: 99%
See 2 more Smart Citations
“…RNA-binding proteins, myelin basic protein, and histones are well known substrates for PRMTs. RNA-binding proteins which generate MMA and ADMA include hnRNP-A1 (Kumar et al, 1986;Kim et al, 1997), nucleolin (Lischwe et al, 1982), fibrillarin (Lischwe et al, 1985a;1985b), the Sam68 Src-associated substrate (Bedford et al, 2000), poly(A)-binding protein II (Smith et al, 1999), the NF90 nuclear-binding factor (Tang et al, 2000), interleukin enhancer binding factor 3 (Tang et al, 2000) and the yeast Npl3 protein (Lee et al, 1996;Siebel and Guthrie, 1996). Myelin basic protein (Stoner, 1984) and proteins Increased m ethylation of the cytosolic 20-kD protein is accom panied by liver regeneration in a hepatectom ized rat sen et al, 2001) are substrates known to produce SDMA.…”
Section: Introductionmentioning
confidence: 99%